Mucus sialylation determines intestinal host-commensal homeostasis - ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA; ERTEM ŞAHİNOĞLU, DENİZ (My University, 2022)
Intestinal mucus forms the first line of defense against bacterial invasion while providing nutrition to support microbial symbiosis. How the host controls mucus barrier integrity and commensalism is unclear. We show that terminal sialylation of glycans on intestinal mucus by ST6GALNAC1 (ST6), the dominant sialyltransferase specifically expressed in goblet cells and induced by microbial pathogen-associated molecular patterns, is essential for mucus integrity and protecting against excessive bacterial proteolytic degradation. Glycoproteomic profiling and biochemical analysis of ST6 mutations identified in patients show that decreased sialylation causes defective mucus proteins and congenital inflammatory bowel disease (IBD). Mice harboring a patient ST6 mutation have compromised mucus barriers, dysbiosis, and susceptibility to intestinal inflammation. Based on our understanding of the ST6 regulatory network, we show that treatment with sialylated mucin or a Foxo3 inhibitor can ameliorate IBD.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Histoloji-Embriyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Histology and Embryology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); HÜCRE BİYOLOJİSİ; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); CELL BIOLOGY; İlaç Keşfi; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Hücre Biyolojisi; Kanser Araştırmaları; Biyokimya; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Structural Biology; Molecular Biology; Clinical Biochemistry; Cell Biology; Cancer Research; Biochemistry; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; dysbiosis; glycobiology; human genetic disease; inflammatory bowel disease; intestinal homeostasis; intestinal stem cells; mucus barrier; short-chain fatty acids; sialylation; ST6GalNAc1